Antibacterial Activity of Salvadora persica L. (Miswak) Extracts against Multidrug Resistant Bacterial Clinical Isolates - Al-Ayed, Mohamed Saeed Zayed (Evid Based Complement Alternat Med, 2016)
Much effort has focused on examining the inhibitory effect of Salvadora persica (miswak) on oral microorganisms, but information concerning its antibacterial activity against other human pathogens, particularly multidrug resistant (MDR) isolates, is scarce. Therefore, this study aimed to assess the in vitro antibacterial activities of Salvadora persica L. extracts against 10 MDR bacterial clinical isolates other than oral pathogens. The antibacterial activity of aqueous and methanol miswak extracts was assessed using the agar dilution and minimum inhibitory concentration (MIC) methods. Overall, the 400 mg/mL of miswak extract was the most effective on all strains. The methanol extract exhibited a stronger antibacterial activity against Gram-negative (3.3–13.6 mm) than Gram-positive (1.8–8.3 mm) bacteria. The lowest MIC value was seen for E. coli (0.39, 1.56 µg/mL), followed by Streptococcus pyogenes (1.56 µg/mL). The highest MIC value (6.25, 12.5 µg/mL) was recorded for methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter baumannii, and Stenotrophomonas maltophilia. This study demonstrates, for the first time, the moderate to strong antibacterial activity of miswak extracts against all tested MDR-pathogens. Methanol extract appears to be a potent antimicrobial agent that could be considered as complementary and alternative medicine against resistant pathogens. Further studies on a large number of MDR organisms are necessary to investigate and standardize the inhibitory effect of miswak extracts against these emerging pathogens.